Analisis Respon Guru terhadap Penggunaan Web-based Assessment untuk Menilai Sikap Siswa terhadap Mata Pelajaran IPA - Astalini, Astalini; Darmaji, Darmaji; Kurniawan, Dwi Agus; Jaya, Hermon; Husna, Sri Muslimatul (Integrated Science Education Journal, 2022)
Purpose of the study: The purpose of this study was to determine the results of the teacher's response to the use of web-based assessment as a medium for assessing student attitudes towards science subjects. Methodology: This research uses quantitative descriptive research. The population in this study were all teachers of MTsN 8 Muaro Jambi and SMPN 30 Muaro Jambi. The sample of this study was taken using a total sampling technique of 38 people. The research instrument used was a non-test instrument in the form of a user response questionnaire. The data analysis technique used is descriptive statistics. Main Findings: From the research that has been done, it is found that teachers at MTsN 8 Muaro Jambi have a very good response with a percentage of 68.18%, while users (teachers) at SMPN 30 Muaro Jambi have a good response to the use of web-based assessment used to assessing students' attitudes towards science subjects with a percentage of 68.75%. Novelty/Originality of this study: The novelty of this study is to analyze the teacher's response to the use of web-based assessments to assess students' attitudes towards science subjects. This is because the analysis of user responses with a sample of educators (teachers) especially in the use of web-based assessments used to assess students' attitudes towards science subjects has not been carried out. Therefore, this research will complement the previous research.